The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1039/c5sm03051j
|View full text |Cite
|
Sign up to set email alerts
|

Structural organization of sterol molecules in DPPC bilayers: a coarse-grained molecular dynamics investigation

Abstract: We investigate the structural organization of cholesterol (CHOL) analogues in 1,2-dipalmitoyl-sn-glycero-3-phosphocholine (DPPC) bilayers using coarse-grained molecular dynamics simulations and the MARTINI forcefield. Different sterol molecules are modelled by increasing (CHOLL) or decreasing (CHOLS) the diameter of the sterol beads employed in the MARTINI model of CHOL. At high sterol concentrations, (x sterol = 0.5), typical of liquid ordered phases, we find that the sterol arrangement and sterol-DPPC intera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 45 publications
0
6
0
Order By: Relevance
“…To quantify the intermolecular organisation of our systems we used both the radial distribution function 10 and Voronoi tessellation analysis. This Voronoi approach has been previously employed to identify 2D clusters 46 in lipid bilayers; here we use a 3D version of this method.…”
Section: Cluster Characterizationmentioning
confidence: 99%
“…To quantify the intermolecular organisation of our systems we used both the radial distribution function 10 and Voronoi tessellation analysis. This Voronoi approach has been previously employed to identify 2D clusters 46 in lipid bilayers; here we use a 3D version of this method.…”
Section: Cluster Characterizationmentioning
confidence: 99%
“…Previously, the MARTINI CG simulations showed that the sterol organization and sterol–lipid interactions are strongly influenced by the sterol size . In this work, we examined the influence of the molecular dipole moment on the lateral organization of CHOL and 6-KC in DMPC lipid bilayers.…”
Section: Resultsmentioning
confidence: 97%
“…Previously, the MARTINI CG simulations showed that the sterol organization and sterol−lipid interactions are strongly influenced by the sterol size. 35 In this work, we examined the influence of the molecular dipole moment on the lateral organization of CHOL and 6-KC in DMPC lipid bilayers. The sterol−sterol radial distribution functions (RDFs) were calculated for the head−head and tail−tail pairs at high sterol concentration (40 mol %), respectively, shown in Figure 10.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Specifically, membrane thickness, area per lipid, and average membrane area all decrease with increasing CHOL content (Table S6), in agreement with previously reported data. 98,99 Of note, replacement of 50 mol % DPPC with CHOL reduced area per lipid and membrane area by ∼33%. We did not observe the appearance of CHOL patches in our simulations, with CHOL being distributed uniformly throughout the bilayer, regardless of concentration (Figure 9).…”
Section: Physicochemical Characterization Of Bsa-coated Liposomes 331...mentioning
confidence: 99%